Improvement in the technological feasibility of a web-based dietary survey system in local settings - Jung, Hyun Ju; Lee, Sang Eun; Kim, Dongwoo; Noh, Hwayoung; Song, Sujin; Kang, Minji; Song, Yoon Ju; Paik, Hee-Young (Asia Pacific journal of clinical nutrition, 2015)
The feasibility of a dietary survey tool is crucial for successful nutritional assessment via a community survey and for nutritional epidemiology. In 2012, we identified a newly developed computerized dietary survey system, the Diet Evaluation System (DES), which could be successfully applied to a community survey delivered during home visits using notebook computers when the internet environment was adequate, using either a WiBro modem or a smartphone as a tethered modem. In 2013, we retested DES feasibility using various mobile devices and in a larger number of subjects. We conducted a total of 430 interviews, representing two for each of 215 subjects of various ages, using tablet personal computers (PCs) and laptops. In addition, a group discussion with the interviewers was conducted. The interview success rate was improved to 84% (compared to 67% in 2012). Completing each interview took 14 min 1 s, and data processing was conducted automatically. The subjects' age, gender, and the type of mobile device used influenced the DES interview time. This study implies that the DES is an effective one-stop dietary survey system for use in a local setting. The interviewers' group discussion revealed that a one-stop system using the DES is convenient and that DES optimization for tablet PCs and continued database updating is needed.